The First Amendment, democracy, and romance - Steven H. Shiffrin (Princeton University Press, 2014)
On July 15, 1838, Ralph Waldo Emerson delivered an address to the Harvard Divinity School. The response was outrage. Emerson was not invited to speak again at Harvard for almost thirty years. The outrage was provoked. In speaking against "historical Christianity,"1 Emerson told the "Unitarian clergy to their faces that they were preaching a dead theology."2 If Christ was important for religion, Emerson said, it should be because of what he said and not because of who he was. To emphasize the authority of Christ, rather than the power of his message, was to "corrupt"3 all attempts at communication, to engage in "noxious exaggeration" 4 of the personal, and to adopt "petrified . .. official titles"5 and a "vulgar tone of preaching"6 that "degrade[s] the life and dialogues of Christ,"7 and "kills all generous sympathy and liking."8 Such appeals to authority were denigrated as "appropriated and formal,"9 a "profanation of the soul,"10 an exhibition of the "sleep of indolence" resting amidst the "din of routine."11 Emerson's gesture was not merely a revolt against the use of appeals to authority in Christian preaching. The Divinity School Address expressed and exemplified Emerson's general view that you should respect no authority, no custom, no convention, no habit, no institution unless it makes sense to you. If it does not make sense, Emerson counseled, demanded, insisted that you speak out. Emerson believed that everyone faces the question: "Will you fulfil the demands of the soul or will you yield yourself to the conventions of the world?"12 The Emersonian message was to trust your own intuitions, to speak out in favor of your own ideals, and to oppose the "strait prison-like limits of the Actual,"13 to resist the conventions of the "old, halt, numb, bedrid world.